Hyperspectral Image Processing Technology and Its Application in Visual Communication Design - Dong Wu; Zhengwei Fang (Advances in Multimedia)
In order to improve the effectiveness of visual communication design, this article combines hyperspectral image processing technology to construct a visual communication design system and improves the effect of visual communication design with intelligent methods. Eagerly, this article proposes a general framework for constructing a suitable shock capture scheme in combination with the entropy control method for suppressing shock instability. In addition, considering the guarantee of qualitative and entropy stability, this article adopts a variety of numerical experiments to evaluate the performance of the full-speed domain scheme. The simulation study shows that the visual communication system based on hyperspectral image processing technology proposed in this article has a very good visual communication effect and can effectively improve the visual communication design effect.